Late Presentation of Hypoxic Injury of Brain in an Infant - Regmi, Pradeep Raj; Yadav, Aalok Kumar; Koirala, Bibek; Yadav, Shreelal; Amatya, Isha (Journal of Nepal Health Research Council, 2023)
Perinatal asphyxia is one of the leading causes of hypoxic-ischemic encephalopathy. In a developing country like Nepal, home delivery is the leading cause of perinatal asphyxia. Neuroimaging remains the diagnostic modality of choice. We present a case report of a 10-month-old infant who presented to the pediatric Out-patient-department with complaints of being unable to hold his head and unable to sit without support. Detailed history, physical examination, and developmental assessment along with lab investigation flash visual evoked potentials and Magnetic Resonance Imaging of the brain was performed. Hypoxic ischemic injury has common five types of imaging patterns in neonates. There are a few imaging differentials to be considered while evaluating the case for hypoxic injury. Clinicians and radiologists must go hand in hand to narrow down the possibilities which can fasten the treatment thereby decreasing morbidity and mortality.Keywords: Hypoxic ischemic encephalopathy, Infant, Magnetic Resonance Imaging